Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Spectra-based predictive mapping of soil erodibility and analysis of its influence mechanism: A typical case study for Northeast China - Yuling Shi; Zihao Wu; Pu Shi; Yuanli Zhu (Soil and Tillage Research, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Mitochondria-targeted NIR fluorescent probe for detection of hydrogen sulfide and its application in monitoring food freshness and bioimaging - Yiyan Huang; Zhengkuan Tan; Xiaoyu Zhang; Haichang Ding; Jing Zhang; Chunmei Jian; Yuling Zeng; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

Influence of supports in CuFe-based catalysts for hydrogenation of CO2 to ethanol - Yangqin Liu; Yuling Ma; Xin Pu; Xin Han; Lei Ye; Lingtao Kong; Jiangbing Li; Jian Zhang; Haitao Xu; Xinglong Qin; Jichang Liu (Fuel, 2025)

AIE-based dual-ratiometric chemosensor for detection of sulfur dioxide derivatives and viscosity and its application in food samples and biological imaging - Na Tang; Ruian Sun; Kangshuo Xu; Haichang Ding; Yuling Zeng; Yuan Ji; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

A turn-off xanthene-based fluorescent probe for detection of cysteine and its practical application in bioimaging and food samples - Na Tang; Kangshuo Xu; Ruian Sun; Haichang Ding; Yuling Zeng; Yuan Ji; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2024)

South and Southeast Asia controls black carbon characteristics of Meili Snow Mountains in southeast Tibetan Plateau - Pengfei Chen; Shichang Kang; Yuling Hu; Tao Pu; Yajun Liu; Shijin Wang; Mukesh Rai; Ke Wang; Lekhendra Tripathee; Chaoliu Li (Science of The Total Environment, 2024)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)